Injectable iodine-containing peptide hydrogel for treatment of MRSA infection - Yu Zhang; Haiyan Liu; Weiqi Zhang; Yinghao Ding; Shengyi Zhang; Xiaowan Huang; Jiali Chen; Zhimou Yang; Feng Lin (Bioactive Materials)
Iodine is widely acknowledged for its potent antimicrobial properties. However, its clinical utility is often hampered by its unsatisfactory stability, uncontrolled release of active iodine and toxicity in moist environments. In this study, we report a novel iodine-containing hydrogel (I2@Nap-FFGP) designed for sustained iodine delivery under humid physiological and pathological conditions. I2@Nap-FFGP was fabricated using a self-assembling peptide-based hydrogel containing a proline motif to form a stable iodine complex. The resulting hydrogel exhibited excellent biocompatibility and robust antibacterial effect, it significantly inhibited bacteria-associated endometrial infections in mice and effectively alleviated inflammation. Moreover, the hydrogel successfully restored endometrial architecture and function. Notably, I2@Nap-FFGP remarkably improved pregnancy rates in mice with endometritis owing to its therapeutic effects. Our findings highlight the potential of this innovative hydrogel system for stable iodine application under humid and aqueous physiological conditions, offering a promising platform for future antibacterial therapies in clinical settings.